2006
DOI: 10.4049/jimmunol.177.2.1139
|View full text |Cite
|
Sign up to set email alerts
|

HS1-Associated Protein X-1 Interacts with Membrane-Bound IgE: Impact on Receptor-Mediated Internalization

Abstract: Engagement of the BCR triggers signals that control affinity maturation, memory induction, differentiation, and various other physiological processes in B cells. In previous work, we showed that truncation of the cytoplasmic tail of membrane-bound Ig (mIg)E in vivo resulted in lower serum IgE levels, decreased numbers of IgE-secreting plasma cells, and the abrogation of specific secondary responses correlating with a defect in the selection of high-affinity Abs during the germinal center reaction. We concluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
0
24
0
1
Order By: Relevance
“…Upon interaction with other cellular proteins, its subcellular localization is redistributed, and this may play an important role in modulating different biological activities (19). Vafiadaki et al (38) reported that an association of HAX-1 with phospholamban, a key regulator of contractibility in the heart, leads to redistribution and colocalization of HAX-1 with phospholamban at the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon interaction with other cellular proteins, its subcellular localization is redistributed, and this may play an important role in modulating different biological activities (19). Vafiadaki et al (38) reported that an association of HAX-1 with phospholamban, a key regulator of contractibility in the heart, leads to redistribution and colocalization of HAX-1 with phospholamban at the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…The biological function of HAX-1 was primarily divided into three categories: (i) association with viral proteins for involvement in apoptotic regulation processes, (ii) involvement in cell motility processes, and (iii) acting as a cytoplasmic retention factor. HAX-1 mRNA is expressed ubiquitously in different tissues, including liver (17,19). Several studies have shown that Hax-1 expression is upregulated in different types of tumors (7,14,17,41,42).…”
mentioning
confidence: 99%
“…Previously, we described HAX1 as interaction partner of membrane bound IgE (mIgE) [24]. From that point of view, it would have been of most interest to analyse IgE responses on a Hax1-deficient background.…”
Section: Discussionmentioning
confidence: 99%
“…HS1-associated protein X-1 (HAX-1) notably seems to be associated with the IgE specific YANIL motif (where Y is a potentially phosphorylated tyrosine) of the intra-cellular tail and may influence BCR mediated Ag-internalization and cognate Ag-presentation to T cells [61]. Hematopoietic progenitor kinase 1 (HPK1) was also shown to interact with mIgE and mIgG (but not mIgM) tails and could differentially affect signaling from these receptors [62].…”
Section: Csr and Bcr Class-specific Control Of B Cell Fatementioning
confidence: 99%